Analisis Kebutuhan Pengembangan Journey of Spices Game untuk Meningkatkan Minat Belajar Sejarah Siswa SMK Negeri 4 Padang - Farizky, Annisa; Afriani, Rini (Jurnal Kronologi, 2026)
This study aims to conduct a needs analysis for the development of a learning medium, the Journey of Spices Game, intended to enhance students’ interest in learning history at SMK Negeri 4 Padang. The study was motivated by the low level of students’ engagement in history learning, which is still dominated by lecture-based instruction and conventional media such as textbooks and presentation slides. Such conditions result in students being less motivated and less actively involved in the learning process. The research employed a descriptive qualitative method, with data collected through observation, interviews, and needs analysis questionnaires involving history teachers and tenth-grade students. The findings indicate that students need interactive, visual, and enjoyable learning media to help them understand the topic of the Indonesian spice routes and the arrival of Western nations. Teachers also emphasized the necessity of technology-based innovations that align with the characteristics of digital-native learners. Based on these findings, the development of the Journey of Spices Game is considered relevant as an effective alternative learning medium to increase students’ interest in learning history. This medium not only provides a more engaging and interactive learning experience but also helps students understand historical material contextually, making them more actively involved in the learning process.